The Geochemistry of englacial brine from Taylor Glacier, Antarctica. - B Gardner, Christopher; Lyons, W. Berry Lyons (IEDA: US Antarctic Program Data Center, 2019)
Abstract: Blood Falls is a hypersaline, iron‐rich discharge at the terminus of the Taylor Glacier in the McMurdo Dry Valleys, Antarctica. In November 2014, brine in a conduit within the glacier was penetrated and sampled using clean‐entry techniques and a thermoelectric melting probe called the IceMole. We analyzed the englacial brine sample for filterable iron (fFe), total Fe, major cations and anions, nutrients, organic carbon, and perchlorate. In addition, aliquots were analyzed for minor and trace elements and isotopes including δD and δ18O of water, δ34S and δ18O of sulfate, 234U, 238U, δ11B, 87Sr/86Sr, and δ81Br. These measurements were made in order to (1) determine the source and geochemical evolution of the brine and (2) compare the chemistry of the brine to that of nearby hypersaline lake waters and previous supraglacially sampled collections of Blood Falls outflow that were interpreted as end‐member brines.